Establishing quality in discursive psychology: Three domains to consider. Issue 3 (3rd July 2021) - O'Reilly, Michelle; Kiyimba, Nikki; Lester, Jessica Nina; Edwards, Derek
ABSTRACT: This paper introduces quality markers common to Discursive Psychology (DP) – a qualitative approach for examining talk and text. We offer a guide for researchers using DP and reviewers evaluating DP research studies. Specifically, we describe a framework involving three key domains, including: quality in data collection and management, quality in the process of analysis, and quality as related to validity and reliability. For each domain, we introduce the related quality indicators. In addition, to the lay the foundation, we briefly overview discourse analysis writ large.